New insights on efficiency and productivity analysis: Evidence from vegetable-poultry integration in rural Tanzania - Habiyaremye, Naphtal; Tabe-Ojong, Martin P.; Ochieng, Justus; Chagamoka, Takemore (Elsevier, 2019)
Despite its dependence on agriculture, food production does not seem to match the population increase in Tanzania. Exacerbating the situation, poverty in the light of per capita income keeps increasing making it one of the poorest economies in the world. Recent policy debates have been geared at probing into the situation and seeking ways of reversing this troublesome and disturbing trend. Increasing productivity and improving production efficiency are steps in the right direction of augmenting food production. We collected data from 250 vegetable farmers in the Babati district of Tanzania and assess the efficiency and productivity level of the integration of poultry systems into their vegetable activity. Specifying the Cobb-Douglas functional form in the stochastic production frontier, we find evidence of the direct impact of farm size, fertilizer quantity, labour cost and seed cost on productivity. While younger farmers are observed with the greatest level of efficiency, male farmers are more technically efficient than their female counterparts. Though surprising (because of the historical attribution of women to vegetables), this is somewhat expected as males are better connected in society and have higher access to improved and novel farming technologies and techniques which are relevant in increasing efficiency. The mean technical efficiency of this production system is 0.44 which is sharply below most studies on vegetables. This re-affirms and re-echoes to policy the need for effective policy developments that underscore the use of improved farming technologies.